Assessing the effectiveness of the non-structural measures for river cleaning - Husin, Nor Azilah; Noor, Ahmad Fuad; Saad, Mazni; Mariyanti, Eka (e-International Publishing House, Ltd., UK, 2021)
Klang River is heavily polluted. The state government tries to reduce this issue. The study's objective is to identify river cleaning's effectiveness by the non-structural measures of cross-sectoral collaboration and public outreach programs. A total of 82 usable data from Lembaga Urus Air Selangor (LUAS), Department of Irrigation and Drainage (DID), Klang Local Council (MPK), Shah Alam Local Council (MBSA), and the river community have answered an adapted questionnaire. We employ SmartPLS software for the analysis. The results show that Cross-sectoral Collaboration (CSC) and Public Outreach Program (POP) have significant effects on Effective River Cleaning (ERC).